The optimized carbapenem inactivation method for objective and accurate detection of carbapenemase-producing Acinetobacter baumannii - Zhang, Sirui; Mi, Peng; Wang, Jingdan; Li, Pu; Luo, Kai; Liu, Shuyan; Al-Shamiri, Mona Mohamed; Lei, Jin’e; Lai, Simin; Han, Bei; Chen, Yanjiong; Han, Lei; et al. (Frontiers in Microbiology, 2023)
The modified carbapenem inactivation method (mCIM) recommended by the Clinical and Laboratory Standards Institute is not applicable for detecting carbapenemases in Acinetobacter baumannii. Four currently reported phenotypic detection methods, namely, the modified Hodge test, the mCIM, the adjusted mCIM, and the simplified carbapenem inactivation method (sCIM), did not perform well in our 90 clinical A. baumannii isolates. Thus, the minimal inhibitory concentrations (MICs) of carbapenems and the existence and expression of carbapenemase-encoding genes were detected to explain the results.Carbapenemase Detection in A. baumannii by oCIM 2 According to the E-test, which was more accurate than the VITEK 2 system, 80.0% and 41.1% were resistant to imipenem (IPM) and meropenem (MEM), respectively, and 14.4% and 53.3% exhibited intermediate resistance, respectively. Five β-lactamase genes were found, of which blaOXA-51-like, blaTEM, and blaOXA-23-like were detected more frequently in 85 non-susceptible strains. The expression of blaOXA-23-like was positively correlated with the MIC values of IPM and MEM. Therefore, an improved approach based on the mCIM, designated the optimized CIM (oCIM), was developed in this study to detect carbapenemases more accurately and reproducibly. The condition was improved by evaluating the factors of A. baumannii inoculum, incubation broth volume, and MEM disk incubation time. Obvious high sensitivity (92.94%) and specificity (100.00%) were obtained using the oCIM, which was cost-effective and reproducible in routine laboratory work.